Pengembangan Sistem Informasi Penjualan Terintegrasi berbasis Website menggunakan Payment Gateway (Studi Kasus: Usaha Kuliner Pentol Buto) - Ya'qub Al-Kindi; Widhy Hayuhardhika Nugraha Putra; Issa Arwani (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2021)
Pentol Buto is the brand name for the pentol produced by UD Berkah Usaha Sucipto. Initially, Pentol Buto sold products through outlets. Over time, in order to maintain competitiveness and expand market share, Pentol Buto launched pentol products in frozen food packaging using a sales system through the website. However, transactions on sales through the website require consumers to upload proof of payment to the admin via whatsapp. The transaction is not effective, because it can allow for an error in the number of payments and must be checked manually. Based on these problems, a sales information system is needed with payment automation features through a payment gateway. The architecture of this research system is based on Service Oriented Architecture. System development applies the waterfall method. The requirements analysis and definition stages produce actor identification, use case diagrams, use case scenarios, and activity diagrams. The system and software design stages are translated into sequence diagrams, class diagrams, and physical data models. The implementation and unit testing stages use the CodeIgniter framework. Functional testing using blackbox testing and obtained results with a value of 100%. Non-functional testing uses compatibility testing with the result that the system is compatible with several browsers, namely internet explorer, safari, microsoft edge, iOs, and android. In performance testing using the jMeter application, it was concluded that the more virtual users did not affect the greater the percentage of error values and the average error percentage was 58.69%.